Efektifitas Konsumsi Telur Ayam Rebus Dan Tablet Fe Terhadap Kadar Hemoglobin Pada Ibu Hamil Anemia Di Klinik I Bekasi Tahun 2023 - Sulastri Sulastri; Dewita Rahmatul Amin (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Pregnancy is a physiological and natural process. Based on WHO data in 2020, the global prevalence of anemia in pregnant women throughout the world is 41.8%, which is related to anemia in pregnancy caused by iron deficiency and acute bleeding. Efforts that can be made to overcome anemia are by giving beetroot, pomegranate, dragon fruit or guava juice or you can also consume boiled chicken eggs to increase hemoglobin levels. The nutritional content of chicken eggs is rich in high quality protein. The aim of this research is to determine the effectiveness of consuming boiled chicken eggs and fe tablets on hemoglobin levels in anemic pregnant women at Clinic I Bekasi in 2023. The research method used is the Quasi-experimental Pre-Post Test With Control Group Design method. Sampling was taken with a total sampling of 30 people. Data analysis used frequency distribution and independent t test. This study uses primary data from Hb examination values by researchers. The research results showed that the average increase in Hb in the intervention group was higher than in the control group. The calculated t value (6.768) > t table (2.048). The results of the analysis used the Independent t test with a p-value of 0.000 < 0.05, meaning that Ho was rejected and Ha was accepted, meaning that there was an effect of consuming boiled chicken eggs and Fe tablets on hemoglobin levels in anemic pregnant women at Clinic I Bekasi in 2023.It is hoped that this research will provide material for consideration of non-invasive therapy that can be offered to pregnant women in order to reduce the number of pregnancy complications, especially helping pregnant women have a healthy and happy pregnancy.